2021
DOI: 10.3390/ijms22105155
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PI3K Pathway in Glioma Cell Resistance to Temozolomide Treatment

Abstract: The aim of the study was to investigate the anticancer potential of LY294002 (PI3K inhibitor) and temozolomide using glioblastoma multiforme (T98G) and anaplastic astrocytoma (MOGGCCM) cells. Apoptosis, autophagy, necrosis, and granules in the cytoplasm were identified microscopically (fluorescence and electron microscopes). The mitochondrial membrane potential was studied by flow cytometry. The activity of caspases 3, 8, and 9 and Akt was evaluated fluorometrically, while the expression of Beclin 1, PI3K, Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…As previously described, EPHB3 could inhibit lung cancer cell migration and suppress PI3K/Akt signalling in GBM 27,28 . The decreased EPHB3 expression was correlated with the reduced survival rate of GBM patients, and blocking the PI3K/Akt/mTOR pathway sensitised GBM cells to apoptosis upon TMZ treatment 29 . We next discovered that the overexpression of YTHDF2 decreased the protein and mRNA levels of EPHB3 in T98G and LN229 cells, and the knockdown of YTHDF2 enhanced these levels in T98G/TR and LN229/TR cells (Figure 3a, b).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…As previously described, EPHB3 could inhibit lung cancer cell migration and suppress PI3K/Akt signalling in GBM 27,28 . The decreased EPHB3 expression was correlated with the reduced survival rate of GBM patients, and blocking the PI3K/Akt/mTOR pathway sensitised GBM cells to apoptosis upon TMZ treatment 29 . We next discovered that the overexpression of YTHDF2 decreased the protein and mRNA levels of EPHB3 in T98G and LN229 cells, and the knockdown of YTHDF2 enhanced these levels in T98G/TR and LN229/TR cells (Figure 3a, b).…”
Section: Resultssupporting
confidence: 63%
“…27,28 The decreased EPHB3 expression was correlated with the reduced survival rate of GBM patients, and blocking the PI3K/Akt/mTOR pathway sensitised GBM cells to apoptosis upon TMZ treatment. 29 We next discovered that the overexpression of YTHDF2 decreased the protein and mRNA levels of EPHB3 in T98G and LN229 cells, and the knockdown of YTHDF2 enhanced these levels in T98G/TR and LN229/TR cells (Figure 3a, b). According to RIP experiment, we found that YTHDF2 could bind to the mRNA of EPHB3 (Figure 3c).…”
Section: Effect Of Ythdf2 Expression On Tmz Resistance In Gbm Cellsmentioning
confidence: 85%
“…Moreover, PI3K inhibitors, such as XL765, a dual mTOR and PI3K oral inhibitor, are currently examined in glioblastoma patients and a phase I trial is underway [ 135 ]. The recent study conducted by Zając et al proved that inhibition of the PI3K/Akt/mTOR pathway sensitizes glioma cells to apoptosis upon temozolomide treatment [ 137 ]. Furthermore, epigenetic alterations also play a role in the development of the resistance to EGFR inhibitors.…”
Section: Egfrmentioning
confidence: 99%
“…Supporting this, the pan-PI3K inhibitor, PX-866, has been found to block TMZ-induced autophagy, whilst promoting GBM cell death (103). In addition, the activation of PTEN/PI3K/AKT signaling has been reported to be an essential step in the development of TMZ resistance in GBM cells in a MGMT-dependent manner (104)(105)(106).…”
Section: Oncogenic Lncrnas Promote Tmz Resistance In Gliomasmentioning
confidence: 90%